2009
DOI: 10.1021/je9001202
|View full text |Cite
|
Sign up to set email alerts
|

Complexation Constants of Procaine with β-Cyclodextrin in NaCl Media

Abstract: The complexation constants of neutral and protonated procaine (also called novocaine) with β-cyclodextrin have been obtained as a function of sodium chloride concentration, at 25 °C, using the potentiometric technique with a glass electrode. It was found that the formation of the complex with protonated procaine is not altered by the presence of the salt and the logarithm of the formation constant of the neutral complex increases slowly with ionic strength, varing linearly with salt concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This may be contrasted with the behavior of these LA guests with CB[7] , in which the monocationic forms of procaine, procainamide and dibucaine guests are found to bind exclusively with the triethylammonium groups within the hydrophobic cavity, leaving the neutral portions outside of the cavity near the portal 21. While for the inclusion behavior of monocationic procaine with β‐ CD , a completely contrary binding mode is postulated in which the nonprotonated group is bound and the positive charged moiety lies outside 20e. It is clear for inclusions of monocationic guests with CB[7] that the observed separation of the 1 H NMR resonances of the nonequivalent diastereotopic CH 2 protons of the terminal ethyl groups on the prochiral protonated nitrogen could be attributed to nonequivalent local environments experienced within the cavity upon CB[7] inclusion of these guests.…”
Section: Resultsmentioning
confidence: 99%
“…This may be contrasted with the behavior of these LA guests with CB[7] , in which the monocationic forms of procaine, procainamide and dibucaine guests are found to bind exclusively with the triethylammonium groups within the hydrophobic cavity, leaving the neutral portions outside of the cavity near the portal 21. While for the inclusion behavior of monocationic procaine with β‐ CD , a completely contrary binding mode is postulated in which the nonprotonated group is bound and the positive charged moiety lies outside 20e. It is clear for inclusions of monocationic guests with CB[7] that the observed separation of the 1 H NMR resonances of the nonequivalent diastereotopic CH 2 protons of the terminal ethyl groups on the prochiral protonated nitrogen could be attributed to nonequivalent local environments experienced within the cavity upon CB[7] inclusion of these guests.…”
Section: Resultsmentioning
confidence: 99%
“…in NaCl media at different pH have been determined by Brandariz and Iglesias-Martínez [5]. It has been demonstrated that complex formation of β-CD with the protonated procaine is not altered by NaCl addition, whereas the logarithm of the stability constant of the complexes with neutral species increases linearly with the rise of the salt concentration.…”
Section: Introductionmentioning
confidence: 99%
“…This ability depends on the compatibility of the guest with the size of the conical cylinder cavity of the CD and the affinity in terms of polarity with the hydrophobic wall of the cavity ( 1-3 ). An interesting group of compounds that form this kind of complexes are local anaesthetics that have been studied previously in our laboratory (4)(5)(6)(7)(8). Stability constants of procaine were obtained using a wide variety of techniques (fluorescence or UVvis spectroscopies, electrical conductivity, potentiometry and kinetic experiments) and conditions (4)(5)(6)(7); in the same manner, tetracaine (TCA) was studied by fluorescence spectroscopy ( 8 ) and the corresponding stability constants of the complexes were determined.…”
Section: Introductionmentioning
confidence: 99%